Response of biofertilizers, on the growth and yield of blackgram (Vigna mungo L.) - P. Thamizhiniyan, T. Ravimycin, G. Selvakumar, M. Lenin (Recent Research in Science and Technology, 2009)
An experiment was conducted to determine the effect of biofertilizers on growth and yield of blackgram in field condition. The experiment was a randomized complete block design with five replication. The different inoculation (single and duel) of biofertilizers Azotobacter, Azospirillum, Rhizobium, phosphobacteria were incorporated into the top 15 cm of the soil. During the experiment period the plant samples were analysed, such as root length, shoot length, fresh and dry weight, leaf number, leaf area, root nodules and the biochemical content such as chlorophyll ‘a’, ‘b’, total chlorophyll, carotenoid, protein content, nodules and yield were analysed. The results revealed that addition the combination inoculation of Rhizobium + phosphobacteria significantly increased growth and yield of blackgram compared with control (without biofertilizers).